Assessing the organizational impact of patient involvement: a first STEPP. Issue 4 (9th May 2016) - Kreindler, Sara A.; Struthers, Ashley
Abstract : Purpose: – Patient involvement in the design and improvement of health services is increasingly recognized as an essential part of patient-centred care. Yet little research, and no measurement tool, has addressed the organizational impacts of such involvement. The paper aims to discuss these issues. Design/methodology/approach: – The authors developed and piloted the scoresheet for tangible effects of patient participation (STEPP) to measure the instrumental use of patient input. Its items assess the magnitude of each recommendation or issue brought forward by patients, the extent of the organization's response, and the apparent degree of patient influence on this response. In collaboration with teams (staff) from five involvement initiatives, the authors collected interview and documentary data and scored the STEPP, first independently then jointly. Feedback meetings and a "challenges log" supported ongoing improvement. Findings: – Although researchers' and teams' initial scores often diverged, the authors quickly reached consensus as new information was shared. Composite scores appeared to credibly reflect the degree of organizational impact, and were associated with salient features of the involvement initiatives. Teams described the STEPP as easy to use and useful for monitoring and accountability purposes. The tool seemed most suitable for initiatives in which patients generated novel, concrete recommendations; less so for broad public consultations of which instrumental use was not a primary goal. Originality/value: – The STEPP is a promising, first-in-class tool with potential usefulness to both researchers and practitioners. With further research to better establish its reliability and validity, it could make a valuable contribution to full mixed-methods evaluation of patient involvement.